PENGARUH JARAK PADA KUALITAS CITRA HASIL REKONSTRUKSI MODE FAN BEAM DENGAN GEOMETRI DETEKTOR BERUPA GARIS - Anam, Choirul; Widodo, Catur Edi (BERKALA FISIKA, 2013)
Image recontruction for fan beam mode with line geometry of detectors have been done. Theobject being imaged is the Shepp-Logan phantom with matrix size 50x50. Projections were made forangle 00 to 3600 with angle interval 10. The distance between the rays in the midle of the object (s) isequivalent to 1 pixel. The distance of source to central of object (D) were varied 40,50, 60, 70, 80, 90,100, 110 pixels. Reconstruction of image was carried out by the method of filtered back projection(FBP) with Lek-Ram filter. It is obtained that if the distance of X-ray source and center of the object,smaller than 3/4 diagonal object, the image will be distorted, and if the distance is greater than 6/7diagonal object, the image will be clipped.Keywords: Image reconstruction, fan beam, line geometry of detector